2007
DOI: 10.1152/ajprenal.00219.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 regulates endothelial gene expression and modulates transendothelial migration of leukocytes

Abstract: The mammalian counterpart of the fish calcium-regulating hormone stanniocalcin-1 (STC1) inhibits monocyte chemotactic protein-1- and stromal-derived factor-1alpha (SDF-1alpha)-mediated chemotaxis and diminishes chemokinesis in macrophage-like RAW264.7 and U937 cells in a manner that may involve attenuation of the intracellular calcium signal. STC1 is strongly induced in the kidney following obstructive injury. We hypothesized that STC1 may serve to attenuate the influx of inflammatory cells to the site of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 50 publications
2
51
0
1
Order By: Relevance
“…Furthermore, we have also shown STC1 to regulate the expression of many genes in human endothelial cells. 11 Collectively, these data indicate that STC1 plays a protective role in regulating endothelial cell functions.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, we have also shown STC1 to regulate the expression of many genes in human endothelial cells. 11 Collectively, these data indicate that STC1 plays a protective role in regulating endothelial cell functions.…”
Section: Discussionmentioning
confidence: 85%
“…These discoveries are complementary to recent observations suggesting that STC1 inhibits transendothelial migration of macrophages and T-lymphocytes through quiescent or IL-1␤-activated human umbilical vein endothelial cells (HUVECs) in vitro. 11 In addition, STC1 regulates gene expression in cultured endothelial cells, and is detected on the apical surface of endothelial cells in vivo. We previously showed increased expression of STC1 in cardiac vessels and cardiomyocytes of patients with dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this issue should be revisited by expanded analyses of various subsets of additional tumor stromal cells, such as fibroblasts, pericytes, and neutrophils. These future analyses should also consider recent studies, which have implicated STC1, in noncancer models, as a regulator of inflammation, macrophage mobility, and vascular permeability (39)(40)(41)(42). Interestingly, earlier studies have also shown that hypoxia, a prometastatic stimuli, also leads to the upregulation of STC1 (43).…”
Section: Discussionmentioning
confidence: 88%